Eksistensi Masjid sebagai Sarana Peningkatan Kualitas Pemahaman Syariat Islam dan Peningkatan Kesejahteraan Ummat - Suaidi Suaidi (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to provide an understanding of the religion of Muslims in using mosques as a means of community development. Mosques are not just a means of routine worship such as the five daily prayers, but mosques should be used as centers for community activities that are humanitarian in nature, both social and increasing competence in terms of understanding religious teachings, so that from the mosque a generation of Muslims who have adequate competence in terms of understanding religious texts grow and develop, so that religion is used as a guideline for life in living life in the world. Mosques are also a place for developing the economic empowerment of the community, so that the practice of Islamic law related to financial obligations such as zakat and the hajj can be carried out by the community who can use and utilize the mosque as a means of development.